2023
DOI: 10.1002/pon.6098
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of distress screening in oral cancer clinics in Sri Lanka

Abstract: Objective: This paper describes the initiation of distress screening in oral cancer clinics, among patients with oral cancer in Sri Lanka, addressing the service gap of lack of psychosocial oncology services. This involved validation of the Sinhala version of the Distress Thermometer (DT) and Problem List (PL) as an adjustment disorder (AD) screening tool. Methods:The DT and PL were translated into the Sinhala language and crossculturally adopted by the "modified Delphi" technique. The judgment validity was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
1
5
1
Order By: Relevance
“…There are no studies purely on the prevalence of psychological distress among patients with oral cancer in Sri Lanka. Of the available few studies among patients with other types of cancers, Mudduwa in 2011 reported a prevalence of 30.66% among patients with breast cancer which was similar to the present study finding 40 . However, in this study, the final diagnosis was made by the Consultant Psychiatrist whereas the current study used the Sinhala-validated Distress Thermometer.…”
Section: Despite Limited Research On Psychological Distress Among Pat...supporting
confidence: 90%
See 2 more Smart Citations
“…There are no studies purely on the prevalence of psychological distress among patients with oral cancer in Sri Lanka. Of the available few studies among patients with other types of cancers, Mudduwa in 2011 reported a prevalence of 30.66% among patients with breast cancer which was similar to the present study finding 40 . However, in this study, the final diagnosis was made by the Consultant Psychiatrist whereas the current study used the Sinhala-validated Distress Thermometer.…”
Section: Despite Limited Research On Psychological Distress Among Pat...supporting
confidence: 90%
“…The sample size for the prevalence study was calculated with a Z value of 1.96 at a 95% confidence interval and 0.05 precision. The anticipated prevalence of psychological distress among patients with oral cancer was 30.7% 40 , and for a 10% non-response rate, the sample size for the prevalence study was 355 41 . For the unmatched case-control study the highest sample size gained for the estimated odds ratio of the associated factors was 65 per arm after adjusting for a non-response rate of 5% 42 .…”
Section: Study Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, screening for distress and providing psychosocial supportive care has to be an integral component of quality cancer care 54 . As Sri Lanka has lacked this aspect, initiation of distress screening in oral cancer clinics was introduced 55 . Furthermore, an intervention package introducing psychosocial supportive care was trialled using the existing cadre of public health nursing officer a category of hospital‐ and community‐based health workers with some success 56 …”
Section: Differences Between Districts In the Distribution Of Oral Ca...mentioning
confidence: 99%
“…54 As Sri Lanka has lacked this aspect, initiation of distress screening in oral cancer clinics was introduced. 55 Furthermore, an intervention package introducing psychosocial supportive care was trialled using the existing cadre of public health nursing officer a category of hospitaland community-based health workers with some success. 56 Most oral cancer patients are treated by primary surgical resection and this is done across the nation in accordance with the National Guidelines which, in turn, closely mirror international best practice.…”
Section: Access To Care: Geographical Distribution Of Diagnostic and ...mentioning
confidence: 99%